A comprehensive analysis of the credits obtained by LEED 2009 certified green buildings - Wu, Peng; Song, Y.; Shou, W.; Chi, H.; Chong, Heap Yih; Sutrisna, M. (Elsevier Science Ltd, 2017)
© 2016 Elsevier LtdThe concept of green building has gained rapid recognition recently. Developed by the U.S. Green Building Council, the Leadership in Energy and Environmental Design (LEED) is one of the most successful green building rating systems. Understanding the performance of LEED certified buildings on various LEED credits is therefore important for practitioners and regulatory authorities. This paper analyses the use of LEED 2009 and investigates the credit allocation pattern of 3416 LEED 2009 certified projects. The results show that compared to its previous version LEED v2.2, the point chasing problem in innovation related credits is mitigated. However, energy-related and material-related credits remain difficult for developers to obtain. LEED 2009 certified projects perform differently in water efficiency at the country level. At the state level, the projects perform differently in water efficiency, energy and atmosphere, material and resources, as well as indoor environmental quality. Varied credit achievement patterns are also identified on cross-certification and cross-sector levels. The study offers a useful guidance for practitioners to achieve relevant certification levels and for regulatory authorities to continuously improve the rating system.